Realitas Implementasi Regulasi Laporan Dana Kampanye Pemilihan Kepala Daerah pada Pilgub Sumbar Tahun 2020 - Yuharmafitri yuharmafitri; Indah Adi Putri; Ria Ariany (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The campaign finance report regulation aims to realize the principle of "honest" elections, namely by implementing transparency in the use of campaign funds for Regional Head Elections reported to the public through the KPU. Campaign finance arrangements have been revised several times by the KPU as the organizer of elections in order to realize transparency in the use of campaign funds. But in reality, the transparency of election campaign finance reports has not been fully realized and is only a formality as one of the administrative requirements of election participants. The problem of transparency in reporting campaign funds was found in the 2020 West Sumatra Governor and Deputy Governor Elections for LADK, LPSDK and LPPDK which were submitted to the KPU to be announced to the public as transparency in the use of campaign funds. The purpose of this research article is as input to the KPU in making improvements to the PKPU regarding the Election Campaign Fund Report in the future in realizing transparency in the use of campaign funds. This study uses a literature review analyzed by researchers during the 2020 West Sumatra Governor and Deputy Governor Elections that have been held. The results showed that the Candidate Pair reported LADK campaign funds, LPSDK was not transparent and the last session of LPPDK was announced to the public after the election voting was held so that it could not be input for the public in making choices on polling day.